2010
DOI: 10.1093/cercor/bhq238
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Intermediate Radial Glia in the Tangential Expansion of the Mammalian Cerebral Cortex

Abstract: The cerebral cortex of large mammals undergoes massive surface area expansion and folding during development. Specific mechanisms to orchestrate the growth of the cortex in surface area rather than in thickness are likely to exist, but they have not been identified. Analyzing multiple species, we have identified a specialized type of progenitor cell that is exclusive to mammals with a folded cerebral cortex, which we named intermediate radial glia cell (IRGC). IRGCs express Pax6 but not Tbr2, have a radial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
832
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 581 publications
(881 citation statements)
references
References 92 publications
46
832
3
Order By: Relevance
“…Previous reports on human fetal cortex reported that the OSVZ was populated by two precursors types: bRG‐ basal ‐P and nonpolar IPs (Fietz et al, 2010; Hansen et al, 2010; Reillo et al, 2011; LaMonica et al, 2013; Ostrem et al, 2014). Using 1,1′‐dioctadecyl‐3,3,3′,3 (Dil) deposits on the pia, these researchers detected back‐labeled cell bodies in the OSVZ, leading them to describe only those OSVZ precursors as bRGs that possess a basal process attached to the basal membrane (Fietz et al, 2010; Hansen et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Previous reports on human fetal cortex reported that the OSVZ was populated by two precursors types: bRG‐ basal ‐P and nonpolar IPs (Fietz et al, 2010; Hansen et al, 2010; Reillo et al, 2011; LaMonica et al, 2013; Ostrem et al, 2014). Using 1,1′‐dioctadecyl‐3,3,3′,3 (Dil) deposits on the pia, these researchers detected back‐labeled cell bodies in the OSVZ, leading them to describe only those OSVZ precursors as bRGs that possess a basal process attached to the basal membrane (Fietz et al, 2010; Hansen et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…These morphotypes range from bRGCs with only a basal process, as originally described in multiple species (Fietz et al, 2010; Hansen et al, 2010; Reillo et al, 2011), to bRGCs with only an apical process, bRGCs with both a basal and an apical process (which may contact the cortical ventricular surface, as in bipolar bRGCs, or not) and even bRGCs that dynamically extend and retract apical and basal processes along the cell cycle (Fig. 1; Betizeau et al, 2013; Pilz et al, 2013).…”
Section: Variations On a Mouse Theme: Toward A Global Understandingmentioning
confidence: 92%
“…First, the presence of a prominent OSVZ (and hence the distinction between ISVZ and OSVZ) and a high abundance of bRGCs has been observed across a wide variety of gyrencephalic mammals but in very few lisencephalic cases (Garcia‐Moreno et al, 2012; Kelava et al, 2012; Martinez‐Cerdeno et al, 2012). Second, the relative abundance of OSVZ progenitors in the embryonic cortex has a significant positive correlation with the degree of cortical folding across a variety of species (Fietz et al, 2010; Hansen et al, 2010; Kelava et al, 2012; Pilz et al, 2013; Reillo et al, 2011). Third, models combining phylogeny proximity data with index of gyrencephaly for a wide range of species conclude that lissencephaly emerged from ancestors more gyrencephalic (Kelava et al, 2012).…”
Section: Beyond Cortical Expansion: Gyrificationmentioning
confidence: 99%
“…Basal radial glia (bRG) are a recently described progenitor type, defined as Pax6‐positive, Tbr2‐negative monopolar progenitors that keep a basal process throughout their cell cycle (Fietz et al, 2010; Hansen et al, 2010; Reillo et al, 2011). They normally undergo self‐renewing divisions, either symmetric or asymmetric, generating neurons (as is the case in the mouse: Shitamukai et al, 2011; Wang et al, 2011) or other progenitor types (as in human and ferret: Gertz et al, 2014; Hansen et al, 2010; LaMonica et al, 2013).…”
mentioning
confidence: 99%
“…A recent report has described great morphologic variability in primate bRG: they can present or grow either a single process or two, directed apically and/or basally and not necessarily contacting the apical or basal surfaces of the cortical wall (Betizeau et al, 2013). bRG are present in both lissencephalic and gyrencephalic species, normally in a much higher proportion in the latter (Fietz et al, 2010; Hansen et al, 2010; Kelava et al, 2012; Reillo et al, 2011; Shitamukai et al, 2011; Wang et al, 2011). They have been proposed to play a significant role in the development of gyrencephaly, both as a source of neurons and as a scaffolding element (Borrell and Reillo, 2012; Fietz and Huttner, 2011; Lui et al, 2011); however, their abundance alone does not account for the presence or absence of cortical folding (Kelava et al, 2012).…”
mentioning
confidence: 99%